2022
DOI: 10.1038/s41586-022-04730-0
|View full text |Cite
|
Sign up to set email alerts
|

MCM complexes are barriers that restrict cohesin-mediated loop extrusion

Abstract: Eukaryotic genomes are compacted into loops and topologically associating domains (TADs)1–3, which contribute to transcription, recombination and genomic stability4,5. Cohesin extrudes DNA into loops that are thought to lengthen until CTCF boundaries are encountered6–12. Little is known about whether loop extrusion is impeded by DNA-bound machines. Here we show that the minichromosome maintenance (MCM) complex is a barrier that restricts loop extrusion in G1 phase. Single-nucleus Hi-C (high-resolution chromoso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 78 publications
2
41
0
Order By: Relevance
“…However, while boundaries such as CTCF sites are stationary (6, 811), RNAPs are mobile and can be dynamically controlled by transcriptional regulators. Together with emerging evidence that extrusion might also be obstructed by other mobile complexes such as replication machinery (24, 32), this suggests that in addition to structural functions, cohesin has important dynamic functions in the spatiotemporal organization of the genome.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, while boundaries such as CTCF sites are stationary (6, 811), RNAPs are mobile and can be dynamically controlled by transcriptional regulators. Together with emerging evidence that extrusion might also be obstructed by other mobile complexes such as replication machinery (24, 32), this suggests that in addition to structural functions, cohesin has important dynamic functions in the spatiotemporal organization of the genome.…”
Section: Discussionmentioning
confidence: 94%
“…Extrusion barriers can thus facilitate or suppress functional interactions, such as enhancer-promoter contacts, which can impact differentiation, disease, and other physiological processes (8,(17)(18)(19)(20)(21)(22)(23). Other factors that do not occupy specific genomic positions, such as the replicative helicase MCM, can also act as barriers to loop extrusion (24). These observations raise the question of how chromatin organization by loop-extruding cohesins is shaped by other chromatin-bound factors, some of which may themselves be mobile.…”
Section: Introductionmentioning
confidence: 99%
“…However, CTCF occupancy is not identical in all cell types and in any case does not account for all TADs (Nora et al, 2017; Taylor et al, 2022). Recent studies have shown that non-encoded features as diverse as MCM complex binding (minichromosome maintenance; most famous for replication origin licensing) and DNA double-strand breaks can also be barriers to loop extrusion (Arnould et al, 2021; Dequeker et al, 2022). Thus small modifications to the basic “loop extrusion versus compartmentalization” model could just as easily explain tissue-specific TAD structures.…”
Section: Discussionmentioning
confidence: 99%
“…Single-molecule total internal reflection fluorescence (smTIRF) microscopy has become an indispensable tool to study bio-macromolecular structure and functionality allowing the observation of, for example, molecule position and dynamics. Examples of such studies include kinetic studies of DNA replication (Dequeker et al ., 2022; Ha et al, 2002; Lewis et al, 2020), studies of the polymerization of structural elements like actin (Amann and Pollard, 2001), the direct observation of flagellar motor rotation (Sowa et al, 2005), as well as tracking of processes in vivo (Vizcay-Barrena et al, 2011). To illustrate the use of Mars for the analysis of such datasets, this example shows a typical Mars workflow for smTIRF studies of the kinetics of a fluorescently-labeled RNA polymerase transcribing on an immobilized, promoter-containing, 21 kb DNA molecule (Scherr et al, 2022) ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%